Station Life in New Zealand - Barker, Lady (Mary Anne), 1831-1911 (Salt Lake City, UT : Project Gutenberg, 2004)
"Station Life in New Zealand" by Lady Barker is a collection of letters detailing the experiences of a woman who settles in New Zealand during the late 19th century. Written amidst the backdrop of the early days of colonization, the correspondence captures the adventures, challenges, and daily life of a sheep-farmer's wife as she navigates her new environment. The narrative reflects the joys and trials of adjusting to a life far removed from the comforts of England, providing insight into both her personal journey and the broader context of colonial life. At the start of the book, Lady Barker introduces herself in the preface, acknowledging the potential egotism of her letters but emphasizing their intent to capture the essence of her experiences. The opening portion describes her arduous two-month sea voyage to Melbourne, where she encounters sea-sickness and the monotony of ship life, yet also finds moments of camaraderie among fellow passengers. As Barker arrives in Melbourne, her observations of the city's rapid development fascinate her, illuminating the stark contrast between her new surroundings and her previous life. With vivid descriptions of the various events, social interactions, and local culture, the opening letters set the stage for a deep exploration of colonial life in New Zealand, merging personal anecdotes with broader reflections on society and nature. (This is an automatically generated summary.)
Release date is 2004-07-01
Produced by P. J. Riddick, and David Widger
Keywords: Barker, Lady (Mary Anne), 1831-1911 -- Correspondence; Sheep ranches -- New Zealand; Governors' spouses -- New Zealand -- Correspondence; Country life -- New Zealand -- History; New Zealand -- Biography; New Zealand -- Social life and customs